Dysregulation of miRNA in chronic hepatitis B is associated with hepatocellular carcinoma risk after nucleos(t)ide analogue treatment. (10th October 2018) - Wakasugi, Hideki; Takahashi, Hideaki; Niinuma, Takeshi; Kitajima, Hiroshi; Oikawa, Ritsuko; Matsumoto, Naoki; Takeba, Yuko; Otsubo, Takehito; Takagi, Masayuki; Ariizumi, Yasushi; Suzuki, Michihiro; Okuse, Chiaki; et al.
Abstract: Hepatitis B virus (HBV) infection is a major cause of hepatocellular carcinoma (HCC). Nucleos(t)ide analogue (NA) therapy effectively reduces the incidence of HCC, but it does not completely prevent the disease. Here, we show that dysregulation of microRNAs (miRNAs) is involved in post-NA HCC development. We divided chronic hepatitis B (CHB) patients who received NA therapy into two groups: 1) those who did not develop HCC during the follow-up period after NA therapy (no-HCC group) and 2) those who did (HCC group). miRNA expression profiles were significantly altered in CHB tissues as compared to normal liver, and the HCC group showed greater alteration than the no-HCC group. NA treatment restored the miRNA expression profiles to near-normal in the no-HCC group, but it was less effective in the HCC group. A number of miRNAs implicated in HCC, including miR-101, miR-140, miR-152, miR-199a-3p, and let-7g, were downregulated in CHB. Moreover, we identified CDK7 and TACC2 as novel target genes of miR-199a-3p. Our results suggest that altered miRNA expression in CHB contributes to HCC development, and that improvement of miRNA expression after NA treatment is associated with reduced HCC risk. Highlights: Expression of miRNAs is significantly altered in chronic hepatitis B (CHB). Nucleos(t)ide analogue (NA) treatment restores miRNA expression in CHB. Insufficient recovery of miRNA expression is associated with HCC risk. Altered miRNA expression may be a predictive marker of post-NA HCC risk. Normalization of miRNAs may be an effective strategy for preventing HCC in CHB.